IDENTIFICATION DES PLANTES MELLIFÈRES DE LA ZONE AGROFORESTIÈRE DE L’ECOLE SUPÉRIEURE AGRONOMIQUE DE YAMOUSSOUKRO (CÔTE D’IVOIRE) - Iritie, Bruno Marcel; Wandan, Eboua N.; Paraiso, Armand A.; Fantodji, Agathe; Gbomene, Lucas Lohoué (European Scientific Journal, ESJ, 2014)
The objective of this study was to identify and characterize different plant species pollinated by bees in the agroforestry land of the School of Agronomy of Yamoussoukro, in the framework of the promotion of beekeeping and sustainable agriculture in Côte d’Ivoire. Plants pollinated by bees in a radius of three kilometers around the beehives were recorded, collected and identified. A total of 160 honey plants belonging to 47 families were surveyed. The majority leguminoseae and euphorbiaceae species, accounted for 15% and 7% respectively. Woody species accounted for 61.25% of pollinated species, grasses and vines 31.88%. The vast majority of plants bloom during the rainy season (89%) with white flowers (63%). These species were foraged for nectar and pollens (52%) or for their nectar (25%) or their pollen (23%). The high number of plants foraged in this area indicates the possibility for beekeeping development in this region of Côte d’Ivoire. Similarly, the majority of species visited by bees are cultivated species, indicating the important role played by these insects in crops breeding. Thus, this would participate in the improvement of yields and the increase of agricultural productivity. Flowering of these plants occurs during the rainy season as well as during the dry season so throughout the year, offering a good opportunity to promote beekeeping in this area.